Organizational Inertia and Momentum: A Dynamic Model Of Strategic Change - Kelly, Dawn; Amburgey, Terry L. (Academy of Management Journal, 1991)
Innovation seems to have been one of the key driving factors of the competitiveness and performance of businesses over the last few decades.Innovative enterprises are growing quicker, have higher efficiency, and are more profitable than their less inventive peers" [23].Such results indicate that the capacity of many companies to innovate and renew may be restricted due to either administrative incompetence, contradictory goals, mismanagement, or leadership skills in deficit.However, as competition in hightechnology industries is pacing up within the innovation economy, modern industrial companies are under rising pressure to tune their innovation ability.The goal of this work is to better understand how innovative initiatives are affected by various organizational environments, in this case, the innovation management process and innovation factors within a business.First, the organizational structure of both methods is clarified, focusing on the management form, the organization's orientation towards innovation, team composition, and the process design of innovative projects, to illustrate the differences.Then the impact on the organization of the basic management process, the collaborative variables, and the results are illustrated and contrasted.